Leveraging microalgae utilization for anthropogenic CO2 emission abatement in Malaysian urban centre: Revisiting the sustainable development goal (SDG-13). (February 2023) - Olalere, Olusegun Abayomi; Gan, Chee Yuen; Yap, Pei-Gee; Alenezi, Hamoud; Abdulhasan, Mahmood Jamal; Babalola, Stephen Olufemi
Abstract: Anthropogenic rise in atmospheric CO2 level is a major contributor to global warming thus posing a threat to the rapidly increasing Malaysia's population. An in-depth investigation focusing on the use of microalgae for CO2 abatement and pollution screening in Malaysia is thus necessary. The use of microorganisms like microalgae has been proposed as a means to mitigate the negative effect of anthropogenic CO2 . The advantages of using microalgae for pollution monitoring far exceed the drawbacks. Algal communities rely on CO2 for photosynthesis because of their capacity to absorb and store more CO2 for growth. This explains why algae are often used to clean the air in our communities. This is because they may be used on both a micro and a macro scale to assess the effects of environmental changes over time. Since the usage of specialized measuring devices may be expensive, replacing them with microalgae as a phytoremediation technology is a viable and cost-effective alternative. This can be utilized to quantitatively identify environmental changes, thus allowing stakeholders to make more well-informed decisions to ameliorate the long-term impacts. This is especially critical in industries like agriculture, where climate changes have a greater impact on agricultural yields. This review gives a brief description of how microalgae could be used for environmental assessment and CO2 abatement relying on Malaysia as a case study. Highlights: SDG-13 focuses on reducing CO2 emissions which is a key driver of global warming. Microalgae have shown remarkable ability to absorb CO2 from the atmosphere directly. Malaysia, being Asia's third-highest CO2 emitter, has prompted major concerns. This study elucidated the microalgae CO2 control potential in Malaysian urban centre.